Implementation of Physical Education, Sports, and Health Learning Programs at the Elementary Special School Level - Didit Pamungkas; Adewole Rufus Sunday; Annerie Kruger (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the implementation of Physical Education, Sports, and Health learning programs at the elementary special school level in Special School Negeri Semarang, focusing on learning planning, implementation, evaluation processes, adaptive teaching strategies, and challenges faced in providing inclusive physical education for students with special needs. Methodology: This study employed a descriptive qualitative approach with a case study design. Data were collected through semi-structured interviews, classroom observations, and documentation techniques involving school principals, classroom teachers, Physical Education, Sports, and Health teachers, and students with special needs. Research instruments included interview guidelines, observation sheets, and documentation checklists. Data were analyzed using the Miles and Huberman interactive analysis model through data reduction, data display, and conclusion drawing techniques. Main Findings: The findings revealed that the implementation of Physical Education, Sports, and Health learning programs had generally applied adaptive educational practices adjusted to students’ characteristics and needs. Teachers modified learning methods, movement activities, and assessment systems to support student participation and motor development. Novelty/Originality of this study: The novelty of this study lies in its comprehensive analysis of adaptive Physical Education, Sports, and Health learning programs through integrated examination of planning, implementation, and evaluation aspects within special school contexts. This study provides a holistic understanding of adaptive physical education practices, emphasizing teacher collaboration, curriculum modification, individualized learning approaches, and flexible assessment systems supporting inclusive education for students with special needs.